Global Citizenship Education: Towards a Critical Moral Pedagogy - Auh, Yoonil; Kim, Chanmi (Social Education Research, 2024)
This study explores the implementation of critical moral pedagogy (CMP) within Global Citizenship Education (GCED) in two schools and a community center in Seoul, South Korea. Over the course of a semester, a mixed-method approach was utilized, encompassing qualitative interviews with educators, focus groups with students, participant observations, and quantitative surveys. By analyzing diverse educational settings, the research uncovers common challenges and effective strategies for integrating CMP within GCED. The findings underscore the significance of context-specific GCED curricula and the value of strong researcher-school collaborations in enhancing students’ global citizenship awareness, critical thinking skills, and social justice orientation. This study provides valuable insights for educators seeking to inspire transformative actions and advance a more equitable and sustainable world.